MODERN MODELS OF PERSONNEL MANAGEMENT: COMPARATIVE ANALYSIS OF RUSSIAN AND FOREIGN EXPERIENCE - Lev Ushvitskiy; Anna Ter-Grigor'yant (Вестник Северо-Кавказского федерального университета, 2022)
The article substantiates the usefulness of the qualitative characteristics of development effectiveness polystructural enterprise as a whole and its separate subdivisions; methodical approaches to the analysis of the efectiveness of economic entities gas producing sector, considered as polystructural formation; proposed tools of structural and dynamic analysis of the efectiveness of the organization polystructural gas industry.